2020
DOI: 10.3390/cancers12040840
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Immunity Linked to Recognition of Antigens Shared by Neural Crest-Derived Tumors

Abstract: In the adult, many embryologic processes can be co-opted by during cancer progression. The mechanisms of divisions, migration, and the ability to escape immunity recognition linked to specific embryo antigens are also expressed by malignant cells. In particular, cells derived from neural crests (NC) contribute to the development of multiple cell types including melanocytes, craniofacial cartilage, glia, neurons, peripheral and enteric nervous systems, and the adrenal medulla. This plastic performance is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 119 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…In premalignant cells, TGF-β served as a tumor suppressor by inhibiting cell proliferation and facilitating apoptosis, whereas, in advanced tumors, TGF-β facilitated metastasis and induced a protumor immune microenvironment ( David and Massagué, 2018 ). Donato et al (2020) suggested that proliferation and migration of neural crest-derived cells involved the activation of the EMT pathway. Schomberg et al (2020) found that luteolin-mediated inhibition of melanoma cell growth may involve simultaneously affecting various pathways such as the ECM, oncogenic signaling, and immune response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In premalignant cells, TGF-β served as a tumor suppressor by inhibiting cell proliferation and facilitating apoptosis, whereas, in advanced tumors, TGF-β facilitated metastasis and induced a protumor immune microenvironment ( David and Massagué, 2018 ). Donato et al (2020) suggested that proliferation and migration of neural crest-derived cells involved the activation of the EMT pathway. Schomberg et al (2020) found that luteolin-mediated inhibition of melanoma cell growth may involve simultaneously affecting various pathways such as the ECM, oncogenic signaling, and immune response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, as shown in Figure 3, the Hematoxylin and Eosin (H&E) stained cytological preparations revealed the presence of bulky, polinucleated or spindled cell atypical elements (Figures 3A, B). In addition, these atypical cells found in the blood resulted, at the immunohistochemical analysis performed through methods previously described ( 14), positive for the expression of the astrocytes markers S-100 (Figures 3C, D) and glial fibrillary acidic protein (GFAP) (Figures 3E, F) (14,15). A section of brain human tissue was used as internal positive control.…”
Section: Case Presentationmentioning
confidence: 95%
“…Biomolecular pathways and cell culture plays a pivotal role in cancer research (9)(10)(11)(12). However, culture-induced changes in biological properties of tumor cells might profoundly affect research reproducibility and translational potential (13)(14)(15). For this reason, the cytological preparations we used in this diagnostic procedure were prepared with a protocol of shorttime in vitro expansion, which we have widely shown to maintain phenotypic and genotypic features of CTCs (6)(7)(8)(9).…”
Section: Case Presentationmentioning
confidence: 99%
“…The prognosis is varied, ranging from spontaneous regressions of the disease, neuroblastoma can change into more differentiated ganglioneuromas or have a clearly aggressive course with poor survival [7]. Tumor regression is an unknown process, but may be due to expression of the nerve growth factor (NGF) receptor TrkA, which promotes differentiation in Segments of neural crest with relative adult tissues and pathologies derivate [2].…”
Section: Neuroblastomamentioning
confidence: 99%
“…Hence, neural crest cells have a multipotent differentiation potential. From these cells originate neurons and glial cells, melanocytes, Schwann cells, parafollicular cells of the thyroid, cells of the adrenal medulla, endothelial cells of large vessels and some components of the connective and skeletal tissue of the head [2] (Figure 1). Based on these concepts, the tumors that develop from the cells of the neural crest represent a very varied and heterogeneous group of neoplasms, these can affect different body locations where the neural crest cellsderived are normally present.…”
Section: Introductionmentioning
confidence: 99%